The effect of brolucizumab on diabetic macular edema and ischemia; a real-world analysis - Chronopoulos, Argyrios; Vidal-Oliver, Lourdes; Sas, Lea K.; Holzwarth, Jakob; Schutz, James; Hattenbach, Lars-Olof (European journal of ophthalmology, 2025)
Objective - The response to intravitreal brolucizumab on diabetic macular edema (DME) and macular ischemia was studied in treatment-refractory and treatment-naïve patients. - Methods - Patients with either recalcitrant (group 1) or treatment-naïve (group 2) DME were studied before and after intravitreal brolucizumab. All patients underwent a comprehensive ophthalmological examination including optical coherence tomography (OCT) and OCT-angiography (OCT-A). We compared the DME and macular/choriocapillaris ischemia before and after the loading dose. - Results - A total of 33 eyes of 26 patients were examined. 18 eyes were switched to brolucizumab, 15 eyes were treatment naive. All eyes responded with anatomical and functional improvement: group 1: 391 vs 298 μm (p = 0.005), 0.6 ± 0.4 logMAR vs. 0.4 ± 0.4 logMAR) (p = 0.01), group 2: 430 vs 281 μm (p = 0.0007), 0.5 ± 0.2 logMAR vs. 0.2 ± 0.2 logMAR (p = 0.004). In group 2 there was also significant improvement in retinal vascular parameters, especially in the central and inner circles of the ETDRS grid: central capillary density 6.55 vs 9.03 mm/mm2 (p = 0.008), inner 11.2 vs 13, 9 mm/mm2 (p = 0.02), central perfusion density 15.5% vs 20.7% (p = 0.02). Choriocapillaris flow deficit (CCFD%) also improved after the loading dose (40.3 vs. 35.3, p = 0.03). Although not statistically significant, there was also an improved foveal circularity. - Conclusion - Intravitreal brolucizumab leads to significant functional and anatomical improvement in diabetic macular edema and has also a beneficial effect on macular ischemia as shown by improvement in both retinal and choroidal perfusion.